Performing arts and the royal courts of Southeast Asia. volume 2: pusaka as performed heritage - Santaella, Mayco Axel * (BRILL, 2024)
This publication brings together current scholarship that focuses on the significance of the performing arts heritage of royal courts in Southeast Asia. The contributors consist of both established and early-career researchers working on traditional performing arts in the region and abroad. The second volume, Pusaka as Performed Heritage, comprises chapters that problematise royal court traditions in the present century with case studies that examine the viability, adaptability, and contemporary contexts for coexisting administrative structures.